RESPON PEMBERIAN PGPR (Plant Growth Promoting Rhizobacteria ) TERHADAP PERTUMBUHAN VEGETATIF TANAMAN CABAI CAPLAK (Capsicum annum L.) - Warsito, Kabul (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2022)
Research on the Response of PGPR (Plant Growth Promoting Rhizobacteria) to Vegetative Growth of Chilli (Capsicum annum L.) was conducted from July to September 2021 in Klambir V Kebun Village, Hamparan Perak District, Deli Serdang Regency. The purpose of the study was to determine the effect of PGPR on the growth of several vegetative organs of tick chili. The method used in this study was a completely randomized design (CRD) with 8 treatments. Parameters observed in this study were plant height, number of leaves, number of branches. The results showed that giving PGPR to chili peppers had no significant effect on plant height. The highest average plant height of 22.74 cm was found in the PGPR treatment at a dose of 200 mL/liter. Meanwhile, the effect of PGPR on the number of leaves gave an insignificant different effect. The best concentration was also shown by treatment with a dose of 200 mL/liter with an average number of leaves of 6.80 leaves. The effect of giving PGPR on the number of branches gave very significantly different results. The best concentration was also shown by treatment with a dose of 200 mL/liter with an average of 3.00.